Undistracted : capture your purpose, rediscover your joy - Goff, Bob (Nelson Books, an imprint of Thomas Nelson, 2022)
Through his pithy and inspiring storytelling that has endeared him to millions, New York Times bestselling author Bob Goff reassures readers that they can harness today's distractions, follow Jesus' example, and find focus, purpose, and joy.